Dinamika Pertumbuhan Hutan Pada Areal Pt Wijaya Sentosa - Tuharea, Ade Fachrianto Raipatty; Murdjoko, Agustinus; Lense, Obed N. (Publikasi Indonesia, 2025)
This study investigates the dynamics of forest stand structure and growth in a post-logging area within the concession of PT Wijaya Sentosa. located in the karst-dominated highlands of Papua. Indonesia. The analysis focuses on the transition of tree diameter classes over a 71year monitoring period. highlighting a significant shift in population structure from small diameter to large diameter classes. The mortality rate remained low (<1%), while recruitment accounted for 32% of the total individuals, suggesting strong regenerative capacity and ecological resilience. Spatial distribution analysis using Kolmogorov-Smirnov tests indicated a shift from normal to non-normal distribution after 2018, likely due to stand structural changes and environmental pressures. These findings underscore the importance of dynamic, long-term monitoring in sustainable forest management. Adaptive management strategies such as extended cutting cycles. enrichment planting, and conservation of high-value species-are recommended to support continued forest recovery and biodiversity maintenance. The observed structural transition reinforces the notion that selectively logged tropical forests can maintain high ecological functionality when managed with precision and care.